Does Implementing a Regime of Dexamethasone Before Planned Cesarean Section at Term Reduce Admission With Respiratory Morbidity to Neonatal Intensive Care Unit? A Randomized Controlled Trial. Issue 7 (July 2018) - Nooh, Ahmed Mohamed; Abdeldayem, Hussein Mohammed; Arafa, Eisa; Shazly, Sherin Attia; Elsayed, Hany; Mokhtar, Wesam A.
Abstract : (Abstracted from J Matern Fetal Neonatal Med 2018;31:614–620) Planned cesarean section (CS) has been found to lead to significantly higher rates of overall neonatal respiratory morbidity than intended vaginal delivery. Various etiologies for these complications have been proposed such as iatrogenic prematurity with surfactant deficiency and an absence of hormonal and physiological changes necessary for proper lung functioning in infants delivered by planned CS.